2017
DOI: 10.1038/srep39717
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature atomic layer epitaxy of AlN ultrathin films by layer-by-layer, in-situ atomic layer annealing

Abstract: Low-temperature epitaxial growth of AlN ultrathin films was realized by atomic layer deposition (ALD) together with the layer-by-layer, in-situ atomic layer annealing (ALA), instead of a high growth temperature which is needed in conventional epitaxial growth techniques. By applying the ALA with the Ar plasma treatment in each ALD cycle, the AlN thin film was converted dramatically from the amorphous phase to a single-crystalline epitaxial layer, at a low deposition temperature of 300 °C. The energy transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 35 publications
5
61
0
Order By: Relevance
“…Due to the relatively low temperature, the remaining N–H bonds from N 2 H 4 are dominant after ligand exchange with TMA, resulting in the lower GPC results [ 31 ]. The R.I. of AlN film deposited at 350 °C is 1.98, which is close to the reported values of high-quality AlN films [ 32 , 33 , 34 ].…”
Section: Resultssupporting
confidence: 87%
“…Due to the relatively low temperature, the remaining N–H bonds from N 2 H 4 are dominant after ligand exchange with TMA, resulting in the lower GPC results [ 31 ]. The R.I. of AlN film deposited at 350 °C is 1.98, which is close to the reported values of high-quality AlN films [ 32 , 33 , 34 ].…”
Section: Resultssupporting
confidence: 87%
“…The presented GIXRD results are also supported by the density, roughness, and Al/N ratio results which were higher for films showing the lowest FWHM thus indicating a higher degree of crystallinity (especially the PA_25V and the PA_300C). In previous PEALD AlN studies, the degree of crystallinity has been shown to extend from amorphous 7,24 to polycrystalline 8,26 and even to the epitaxial grade [the (002) rocking curve being 144 arcsec] 44 depending on the process parameters, chosen substrate, surface treatment, and PEALD reactor setup. These aspects affect the impurity levels which in turn are known to affect crystallinity.…”
Section: Crystallinitymentioning
confidence: 99%
“…For application in nanoelectronics, it is essential to have atomic precision in materials manufacturing. Over the last decades ALD proved to be a relatively affordable method with high scalability and repeatability while also providing the necessary precision of the atomic layer for films fabrication at the nanoscale level [15][16][17].…”
Section: Introductionmentioning
confidence: 99%